Exploitable Potential, Theoretical Potential, Technical Potential, Storage Potential and Impediments to Development of the Potential: The Nepalese Perspective - Shrestha, Hari Man (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Exploitable potential is an ultimate derivable of theoretical potential, technical potential and/or storage potential. A number of hurdles come across when a potential site has to be exploited, thus, all theoretically and/or technically available potential cannot actually be developed/ exploited. Nepal is not an exception in this respect. Exploitation of run-of-river schemes has much less hurdle in comparison with storage development. The storage development, particularly the larger scale development, has even international implications, because the benefits of such development spread far beyond the national boundary. In the Nepalese case the downstream country, particularly India, is reluctant to recognize the downstream flow regulation benefits arising from flood-control and dry season flow augmentation. As such the current focus of exploitation of Nepalese hydro-potential should be on run-of-river type development and smaller size storage developments which can easily be materialized without much hurdle, but in a coordinated and well scheduled manner in a way not to hamper the larger storage development at the opportune future dates.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 19Page:1-5